Identifying Local Knowledge and Meaning of Rural Farming Communities in the Modernization Era - Irmayani, Irmayani; Darmawan; Poornika Kumari Seelagama; Feby Sri Sukmayana; Sitti Rahbiah; Andi Besse Dahliana (Universitas Hasanuddin, 2023)
This study aims to identify local knowledge and the meaning of the rice farming community in the modernization era and to find out the concept of symbolic interactionism in the meaning of local knowledge of the farming community in Sabbangparu District, Wajo Regency. This study uses a qualitative descriptive approach and is described through phenomenological studies and interpretation of meaning through the concept of symbolic interactionism by taking informants purposively and snowball sampling. Data collection was carried out in three stages, namely participant observation, in-depth interviews, and documentation. The results showed that local knowledge in rice farming activities in Sabbangparu District, Wajo Regency has begun to be abandoned, but there are local knowledge systems that are still maintained in the modernization era as it is today including Mattanra Esso (Determination of Good Days) and Mappadendang (Harvest Festival). Local knowledge that is still maintained contains a meaning that is very difficult for the farming community in Sabbangparu District, Wajo Regency to abandon, but some other local knowledge has begun to be abandoned, this is based on the thinking of the farming community which has become more rational.